Avaliação da política pública de formação policial da AESP/CE no período 2011-2023 - Torres, Tayana Cibele Canafístula (2024)
This study investigates public police training policies, with a particular focus on the State Academy of Public Security of Ceará (AESP/CE), during the period between 2011 and 2023. From an interdisciplinary theoretical-methodological perspective that articulates police education, management of public security, human rights and Sustainable Development Goal 16, exploratory qualitative research employs a combination of field research, insider participant observation, documentary analysis and in-depth conversations. The objective is to evaluate the design of the administrative structure of AESP/CE by examining its actions to promote integration between military and civilian training in the preparation of public security professionals. Analysis of current educational policies and practices highlights the need to align police training with democratic principles and respect for human rights, in line with United Nations SDG 16, which aims to promote peaceful and inclusive societies for sustainable development. The results, constructed through content and discourse analyses, indicate the urgency of educational reforms that not only overcome the traditional dichotomy between military and civilian training, but also promote an educational paradigm centered on respect for human rights, social justice and in the culture of peace.